THE CORRELATION BETWEEN PARITY AND BABY WEIGHT TO THE INCIDENCE OF POSTPARTUM HEMORRHAGE - Ristanti, Adenia Dwi; Lutfiasari, Dessy; Pradian, Galuh; Pujiastuti, Sri Endang (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: The most dominating factors of maternal deaths is postpartum hemorrhage, which predominantly caused by parity 4.20%, baby weight 3.55%, retention 1.94%, uterine atony 1.29%, and age of mother 1.94%. Aims: The purpose of this study was to determine the correlation between parity and baby weight on the incidence of postpartum hemorrhage at Gambiran hospital Kediri in 2015. Methods:This is a quantitative research using Rank Spearman and multiple logistic regression. statistics test. The population of this study is all women who giving birth at Gambiran hospital Kediri from January- March 2015, with total 309 respondents. By using simple random sampling technique, 175 respondents was selected for this study.Â Results: Results showed most of respondents (70.9%) gave birth normally and more than a half (51.4%) have experienced with postpartum hemorrhage. Its highly significant that lower baby weight and parity have correlated with the incidence of postpartum hemorrhage,while the most influence of postpartum hemorrhage was lower baby weight (4 times more risk) and 3.3 more risk for parity. Conclusion: The parity and lower baby weight have positive correlation and influences with postpartum hemorrhage. Based on the results of the study the health workers expected to improve the quality of service on antenatal to decrease the number of postpartum hemorrhage.Â